Factors Influencing Nurse Job satisfaction and the Consequent Effects on Patient Care Quality: A Scoping Review - Sunati, Nirmala; Komariah, Maria; Agustina, Hana Rizmadewi (Journal of Health and Nutrition Research, 2025)
Nurses play a pivotal role in determining the quality of healthcare services. Job satisfaction among nurses not only influences their professional performance but also directly affects the quality of patient care. Dissatisfaction may lead to burnout, errors, and decreased patient safety. This study aimed to identify and analyze the factors related to nurses’ job satisfaction and to explore how these factors impact the quality of patient services. A scoping review was conducted using the PRISMA-ScR guidelines. Literature searches were performed through PubMed, CINAHL, and Google Scholar based on the PCC framework. Articles were selected through a systematic screening process, and data were extracted and analyzed thematically. The review identified 25 key factors associated with nurses’ job satisfaction, categorized into four main domains: (1) organizational and leadership factors, (2) individual nurse characteristics, (3) work environment, and (4) professional development and practice. Supportive leadership, organizational commitment, and recognition were strongly associated with higher satisfaction. Improving nurses’ job satisfaction through targeted strategies is a critical component for ensuring high-quality patient care and favorable outcomes. Strategies such as enhancing work conditions, fostering leadership support, and providing development opportunities are vital for strengthening both nurses' well-being and patient outcomes.